Supporting the Assessment of Collaborative Design Activities in Multi-tabletop Classrooms - Granda, Roger X.; Echeverria, Vanessa; Chiluiza, Katherine; Wong-Villacres, Marisol (2015 Asia-Pacific Conference on Computer Aided System Engineering, 2015)
The present study describes a proposed multitable top system for supporting collaborative database design activities in the classroom. Additionally, two experiments were conducted to evaluate students' and teachers' perceptions of the proposed system potential on aspects of group work assessment such as: ease of grading individuals as well as groups, equality of students' participation, and, capability to accurately reflect individual contributions. Ten educators and 22 students from a Computer Science program participated in the experiments. The findings of this work show that the use of the proposed system impacted positively on the educators' perception about the ease of grading individuals and groups. In addition, distinguishing users in collaborative group work is key for decreasing social-loafing. The results suggest that the proposed system does have potential to support a better group work assessment.